The Influence of Leadership, Motivation, and Work Discipline on Work Productivity of Grapari Medan Putri Hijau Customer Service Section - Catherine Krispina Br Ginting; Muhammad Alfahmi (International Journal of Management, Economic and Accounting, 2024)
The research analysis aims to find out whether leadership, motivation and work discipline influence work productivity. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 37 respondents. Primary data collection uses a questionnaire. The research results show that leadership has a partially positive and significant effect on work productivity. Motivation does not have a partially significant effect on work productivity. Work discipline has a partially positive and significant effect on work productivity. Leadership, motivation and work discipline simultaneously have a positive and significant effect on work productivity.